2018
DOI: 10.1177/1179551417751611
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ramadan Education and Knowledge Among Diabetic Patients

Abstract: Background:During Ramadan, Muslims fast from dawn until dusk for one lunar month every year. Most of the Muslim patients with diabetes are unaware of the potential complications that can occur while fasting, such as hypoglycemia. The aim of this study is to assess the the patient education level and patients’ overall awareness of any possible complications that could occur while fasting during Ramadan and to determine how these patients deal with these complications.Methods:We conducted a cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…This study was carried out among 125 type 2 diabetes attending RUHDC and more than half of the patients in this study had poor hypoglycemia symptoms knowledge and these findings was less than reported by Almalki et al [17] who reported 85% of patients had sufficient knowledge about the symptoms of hyperglycemia and this high percent is attributed to the fact that more than half of his patients received information about diabetes management from medical providers. On the other hand, Kazi and his colleagues [18] reported only 17.2%, whilst El-Khawaga from Egypt reported 48.1% [19].…”
Section: Discussionmentioning
confidence: 54%
“…This study was carried out among 125 type 2 diabetes attending RUHDC and more than half of the patients in this study had poor hypoglycemia symptoms knowledge and these findings was less than reported by Almalki et al [17] who reported 85% of patients had sufficient knowledge about the symptoms of hyperglycemia and this high percent is attributed to the fact that more than half of his patients received information about diabetes management from medical providers. On the other hand, Kazi and his colleagues [18] reported only 17.2%, whilst El-Khawaga from Egypt reported 48.1% [19].…”
Section: Discussionmentioning
confidence: 54%
“…To achieve the objectives of this study, the investigators constructed a questionnaire in Arabic language based on relevant studies. [89101112131415] The questionnaire consisted of five parts as following: the first part was about the demographic variables (age, sex, educational status, marital status. The second part dealt with patient health data (type of DM, duration, history of chronic health problems, types of drugs in use).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the seriousness of hypoglycemia and its bad consequences among diabetics during Ramadan, it still needs more research as few studies were conducted in Saudi Arabia to explore this subject. [7891011] To our current knowledge, there was no single study conducted on this topic in southern region of KSA. This study aims to explore the incidence of hypoglycemia and its risk factors among diabetic patients during Ramadan in Abha city, Aseer region, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Low socioeconomic status (SES), place of residence, education, sex, level of awareness, poor nutrition, poor health behaviors (eg, tobacco use), a “fatalistic attitude”, and self‐care affect prevention, and can lead to poor compliance with treatment, poor control, and increased complications of diabetes in developing countries . Inconsistencies regarding diets in the management of diabetes (eg, religious fasting and traditionally held misconceptions) hinder the achievement of proper glycemic control (Table ).…”
Section: Managementmentioning
confidence: 99%